Adverse drug reactions to atezolizumab in combination with bevacizumab in hepatocellular carcinoma patients: an analysis of the food and drug administration adverse event reporting system database - Wanming He; Lihua Tong; Yanling Yuan; Xia Yang; Wen Yang; Xingxi Pan (Frontiers in Pharmacology)
PurposeThe objective of the study is to systematically identify and evaluate the adverse drug reactions (ADRs) associated with the combination therapy of systematically and bevacizumab in patients with unresectable hepatocellular carcinoma (HCC).Patients and methodsData were extracted from the Food and Drug Administration (FDA) Adverse Event Reporting System FDA Adverse Event Reporting System database. Disproportionality analysis was conducted using the reporting odds ratio (ROR), proportional reporting ratio (PRR) and Bayesian confidence propagation neural network (BCPNN) of information components (IC). Time-to-onset (TTO) profiles were analyzed using the Weibull shape parameter (WSP) test, while cumulative incidences were assessed using the Kaplan‒Meier method. Valuable preferred term (PT) signals were identified for designated medical event (DME) screening, comparing these signals with system organ class (SOC) analysis.ResultsA total of 2,831 adverse events (AEs) reports were identified in the FAERS database, of which 124 positive AEs were detected across multiple SOCs. The median TTO of AEs was 43 days, with the highest proportion occurring within 0–30 days of TTO (n = 450, 41.17%). The WSP test indicated that patients with abnormal hepatic function and hepatic failure exhibited early failure-type profiles. Ten PT signals consistent with those on the DME list were identified, involving six SOCs.ConclusionOur study provides valuable pharmacological insights for early clinical intervention in managing ADRs and offers significant clinical benefits for HCC patients undergoing combination therapy with atezolizumab and bevacizumab.